2012
DOI: 10.1590/s0102-05362012000100016
|View full text |Cite
|
Sign up to set email alerts
|

Processing quality of potato tubers produced during autumn and spring and stored at different temperatures

Abstract: BISOGNIN DA. 2012. Processing quality of potato tubers produced during autumn and spring and stored at different temperatures. Horticultura Brasileira 30: 91-98. ABSTRACTThe objective of this work was to access processing quality of potato clones (Solanum tuberosum) Asterix, SMINIA793101-3, and Missaukee cultivated during spring and autumn growing seasons and stored at 4, 8, 12, or 25ºC. Clones grown in spring had shorter dormancy than clones grown in autumn. Potato tubers grown in spring and autumn and store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
1
12
0
4
Order By: Relevance
“…Color is also an important quality attribute which influences the acceptability of fried products (Nourian et al, 2003). Golden yellow color is considered to be the best for high quality potato chips (De Freitas et al, 2012). Specific gravity is positively correlated to dry matter and starch content in several researches.…”
Section: Introductionmentioning
confidence: 99%
“…Color is also an important quality attribute which influences the acceptability of fried products (Nourian et al, 2003). Golden yellow color is considered to be the best for high quality potato chips (De Freitas et al, 2012). Specific gravity is positively correlated to dry matter and starch content in several researches.…”
Section: Introductionmentioning
confidence: 99%
“…But as the storage time progressed to 40 and 60 days, there were significant decreases in the dry matter yield and specific gravity. Corroborating this result, Freitas et al, (2012) reported a significant decreasing trend in the specific gravity and dry matter contents of the potato tubers stored for 180 days at 12 o C. The decrease in the potato tuber dry matter and specific gravity in response to the prolonged duration of storage can be attributed to the gradual respiratory biochemical starch breakdown to sugars that is used up to maintain life of the tuber with concurrent production of carbon dioxide and water vapour (Bisognin et al, 2008). Potato tuber dry matter contents and specific gravity are predictors of the potato tubers end use quality.…”
Section: Tuber Dry Matter Content and Specific Gravitymentioning
confidence: 91%
“…Os caracteres matéria seca e amido são correlacionados, uma vez que o amido representa a maior parte da matéria seca do tubérculo (FREITAS et al, 2012). Nesse caso, à medida que as condições de cultivo do verão favorecem o acúmulo de matéria seca, ocorre o aumento do teor de amido.…”
Section: R Esultados E Discussãounclassified
“…II Empresa de Pesquisa Agropecuária e Extensão Rural de Santa Catarina (Epagri), Estação Experimental de São Joaquim, São Joaquim, SC, Brasil. além da condição de armazenamento dos tubérculos (AFFLECK et al, 2012;FREITAS et al, 2012). O teor de matéria seca afeta o rendimento industrial e a textura da batata processada (ROMMENS et al, 2010).…”
Section: Introductionunclassified
See 1 more Smart Citation